Quality of services in health education nurse-led clinics: an Iranian service providers and service recipients experience - Zohre Pouresmail; Fatemeh Heshmati Nabavi; Maryam Rassouli (BMC, 2024)
Abstract Background Patient education is a vital role of nurses in nurse-led clinics(NLCs). Since 2011, independent NLCs entitled health education Nurse-led clinics(HENLCs) have been established in Iran. In order for this newly developed service to be able to perform perfectly in implementation and evaluation, it should be explained based on one of the quality evaluation models. The objective of the study was to determine the dimension of service quality in HENLCs based on service providers' and service recipients' experience. Methods This research is a qualitative study of directed content analysis type conducted between May and November 2020. Twenty-nine participants who had rich experiences in the patient education in HENLCs were interviewed in this study. Asarroodi et al.'s (2018) qualitative content analysis method was used for data analysis, and MaxQDA software was used for data management. We used credibility, dependability, and Confirmability to confirm the trustworthiness of the study's findings. Results In this study service providers including managers, policymakers, decision-makers, nurses, physicians, and service recipients including patients and families participated. Seven generic categories, including (1) a competent and self-motivated nurse educator, (2) an easily accessible and comfortable environment, (3) informational-educational materials and health education equipment, (4) motivational facilities, (5) access to the health education support team, (6) organizational communication supporting the education process, and (7) receiving the patient education fee, constituted the main category of structure. Five generic categories, including (1) assessment and determination of the educational needs of the target group, (2) description of the nurse's duties, (3) teaching-learning methods, (4) patient referral, and (5) the process of preparing and publishing educational content, constituted the main category of process. One generic category called evaluation constituted the main category of outcome. Conclusion Based on the results of this study, it is suggested to managers to pay attention to the dimensions of the quality model of Donabedian (SPO) in setting up and developing the performance of HENLCs, it is recommended that future quantitative studies based on the categories formed in this study evaluate the observance of the dimensions of structure, process and outcome.